EFFICIENT SYSTEM FOR COMPLAINT PORTAL MANAGEMENT USING CLASSIFICATION TECHNIQUE IN DATA ANALYTICS - S, KANIMOZHI; C, DURGHA; SRI B, JEYA; M, MEGADHARSHINI; B, SRUTHI (International Journal of Psychosocial Rehabilitation, 2020)
A mobile-based application has been developed to handle multiple complaints in one portal. This mobile application is used to post complaints about EB, water, transport, and so on. In this mobile application, the user can register and login to the system using his/her user name and password. After login process, the user can post the complaint and forward to appropriate departments